2023
DOI: 10.4093/dmj.2022.0129
|View full text |Cite
|
Sign up to set email alerts
|

Safety of COVID-19 Vaccines among Patients with Type 2 Diabetes Mellitus: Real-World Data Analysis

Abstract: Background:Little is known about the adverse events (AEs) associated with coronavirus disease 2019 (COVID-19) vaccination in patients with type 2 diabetes mellitus (T2DM). Methods: This study used vaccine AE reporting system data to investigate severe AEs among vaccinated patients with T2DM. A natural language processing algorithm was applied to identify people with and without diabetes. After 1:3 matching, we collected data for 6,829 patients with T2DM and 20,487 healthy controls. Multiple logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Additionally, we calculated standardized mean differences (SMDs) across groups to detect any remaining imbalance in the matched samples. Consequently, as presented in Table 1 of our paper [ 1 ], the SMD was <0.001, and a 1:3 PSM ratio was the optimal matching.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, we calculated standardized mean differences (SMDs) across groups to detect any remaining imbalance in the matched samples. Consequently, as presented in Table 1 of our paper [ 1 ], the SMD was <0.001, and a 1:3 PSM ratio was the optimal matching.…”
mentioning
confidence: 76%
“…We appreciate the valuable insights provided by Dr. Ohn in response to our published study titled, “Safety of COVID-19 vaccines among patients with type 2 diabetes mellitus: real-world data analysis” [ 1 ]. We also extend our gratitude to the editor for allowing further discussion on our article.…”
mentioning
confidence: 99%
“…It is worth mentioning that atrial fibrillation is a risk factor only in female patients [ 21 ]. Diabetes is also a study-proven risk factor for IS, with the risk found to be higher in patients with diabetes [ 22 ]. The average interval from vaccination to symptoms is 9 days [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overweight and obese patients are often encouraged to lose weight to improve their diabetes outcomes. A study from Korea, which was published in Diabetes, Obesity & Metabolism, 1 however, have highlighted the important of early weight loss to enhance the likelihood of inducing diabetes remission.…”
mentioning
confidence: 99%